Composicion floristica de un bosque mesofilo del centro de Veracruz, Mexico - Garcia Franco, J.G.=700 1 Castillo Campos, G.
(Es, En)
ilus., 31 ref
Keywords: COMPOSICION BOTANICA; BOSQUES; BIODIVERSIDAD; FRAGMENTACION; MEXICO; BOLETIN DE LA SOCIEDAD BOTANICA DE MEXICO